Metformin and cancer: Technical and clinical implications for FDG-PET imaging - Capitanio, Selene (World J Radiol, 2015)
Metformin is the most widely used hypoglycemic agent. Besides its conventional indications, increasing evidence demonstrate a potential efficacy of this biguanide as an anticancer drug. Possible mechanisms of actions seem to be independent from its hypoglycemic effect and seem to involve the interference with key pathways in cellular proliferation and glycolysis. To date, many clinical trials implying the use of metformin in cancer treatment are on-going. The increasing use of (18)F-2-fluoro-2-deoxy-d-glucose positron emission tomography (FDG-PET) in cancer evaluation raises a number of questions about the possible interference of the biguanide on FDG distribution. In particular, the interferences exerted by metformin on AMP-activated protein kinase pathway (the cellular energy sensor), on insulin levels and on Hexokinase could potentially have repercussion on glucose handling and thus on FDG distribution. A better comprehension of the impact of metformin on FDG uptake is needed in order to optimize the use of PET in this setting. This evaluation would be useful to ameliorate scans interpretation in diabetic patients under chronic metformin treatment and to critically interpret images in the context of clinical trials. Furthermore, collecting prospective data in this setting would help to verify whether FDG-PET could be a valid tool to appreciate the anticancer effect of this new therapeutic approach.